2018
DOI: 10.1111/jai.13667
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish (Danio rerio , Hamilton-Buchanan, 1822) as a model to study bone diseases associated with Rett syndrome

Abstract: Summary Rett syndrome (RTT) is a severe neurological disorder in humans that almost exclusively affects only females. This disease is characterized by an apparent normal growth and intellectual development during the first year of life, followed by a progressive regression in development characterized by loss of purposeful use of the hands, distinctive hand movements, slowed brain and head growth, problems with walking, seizures, and intellectual disability. Mutations in the X‐linked gene methyl‐CpG‐binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…[79][80][81][82] In this respect, functional domains of human MECP2 and zebrafish mecp2 proteins and genomics studies indicate that zebrafish has emerged as an interesting species in reshaping our understanding of MECP2 mutations and clinical parameters impact bone mass in RTT and eventually will evaluate treatments against these human skeletal disorders. 25,79,83,84 A recent proteomic study using the mecp2 Q63X mutant (mecp2-null) zebrafish to examine protein expression changes in mecp2-null versus wild-type larvae and adult zebrafish showed that 20 proteins are differentially expressed between mutant and wild-type fish. 85 The identified proteins are involved in skeletal and cardiac muscle function and redox balance maintenance.…”
Section: Rtt In a Zebrafish Modelmentioning
confidence: 99%
“…[79][80][81][82] In this respect, functional domains of human MECP2 and zebrafish mecp2 proteins and genomics studies indicate that zebrafish has emerged as an interesting species in reshaping our understanding of MECP2 mutations and clinical parameters impact bone mass in RTT and eventually will evaluate treatments against these human skeletal disorders. 25,79,83,84 A recent proteomic study using the mecp2 Q63X mutant (mecp2-null) zebrafish to examine protein expression changes in mecp2-null versus wild-type larvae and adult zebrafish showed that 20 proteins are differentially expressed between mutant and wild-type fish. 85 The identified proteins are involved in skeletal and cardiac muscle function and redox balance maintenance.…”
Section: Rtt In a Zebrafish Modelmentioning
confidence: 99%